2009
DOI: 10.1074/jbc.m109.028753
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-mediated Regulation of Human Lipin 1 Gene Expression in Hepatoblastoma Cells

Abstract: Lipin 1 plays a crucial role in lipid metabolism in adipose tissue, skeletal muscle, and liver. Its physiological role involves two cellular functions: regulation of phosphatidate phosphatase activity and regulation of fatty acid oxidation. In this study, we have demonstrated that lipin 1 gene (LPIN1) expression is regulated by cellular sterols, which are key regulators of lipid metabolism. We have also characterized the sterol-response element and nuclear factor Y-binding sites in the human LPIN1 promoter. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 40 publications
5
51
0
3
Order By: Relevance
“…It is known to be induced by glucocorticoids in adipose tissues and the liver and by ␤-adrenergic signaling in skeletal muscle through the glucocorticoid receptor and the orphan nuclear receptor NOR-1 (40,41). It has also been reported that LIPIN1 is a target of SREBP-1 (sterol regulatory element-binding protein 1) and nuclear factor Y in hepatoblastoma cells (42). While this study was being carried out, one report was published regarding the role of LIPIN1 in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 93%
“…It is known to be induced by glucocorticoids in adipose tissues and the liver and by ␤-adrenergic signaling in skeletal muscle through the glucocorticoid receptor and the orphan nuclear receptor NOR-1 (40,41). It has also been reported that LIPIN1 is a target of SREBP-1 (sterol regulatory element-binding protein 1) and nuclear factor Y in hepatoblastoma cells (42). While this study was being carried out, one report was published regarding the role of LIPIN1 in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 93%
“…HRE 1 is conserved (Fig. 7B) as it is perfectly matched by a potential distal HRE in the mouse Lpin1 promoter region and is found close to the only other known distal regulatory elements, the SRE and NF-Y sites (Ishimoto et al, 2009). Finally, mutation of HRE 1 (Fig.…”
Section: The Human Lpin1 Promoter Contains a Conserved Functional Hrementioning
confidence: 97%
“…Of interest, it has been reported recently that the lipogenic transcription factor SREBP-1 is involved in the regulation of lipin-1 expression (Fig. 3) and that lipin-1 protein is induced by sterol depletion (Ishimoto et al 2009). In addition, lipin-1 gene expression is induced by T0901317, an activating ligand for the LXR (Ishimoto et al 2009).…”
Section: Sirt1 As a Regulator Of Ppara-pgc-1a Directed Gene Expressiomentioning
confidence: 99%
“…3) and that lipin-1 protein is induced by sterol depletion (Ishimoto et al 2009). In addition, lipin-1 gene expression is induced by T0901317, an activating ligand for the LXR (Ishimoto et al 2009).…”
Section: Sirt1 As a Regulator Of Ppara-pgc-1a Directed Gene Expressiomentioning
confidence: 99%